Prognosis method of unfavorable airborne events during flight based on convolutional and recurrent neural networks - Gryshmanov, E.; Kalimulin, T.; Zakharchenko, I. (Національний технічний університет "Харківський політехнічний інститут", 2019)
This paper contains formal problem definition of predicting unfavorable airborne events during flight. Restrictions and assumptions are put into the prognosis method of unfavorable airborne events during flight. Mathematical apparatus used to build prognosis method is suggested. As a basic mathematical apparatus it is suggested to use, recurrent neural networks (RNN) basedon LSTM modules and convolutional neural networks (CNN). Analysis of these neural networks has shown that RNN based on LSTM modules are mostly effective when analyzing structured text, such as report of investigation of airborne accidents. In its turn, CNN are effective when analyzing unstructured text, such as text messages about the flight situation based on the information from external sources. Prognosis method of unfavorable airborne events during flightbased on convolutional and recurrent neural networks is developed. In case of solving the task of prediction of unfavorable airborne events during flight RNN are used for initial setup of the Embedding layer of the structured training data in the process of hybrid neural network training. CNN are used during the direct operation of hybrid neural network model of prediction of unfavorable airborne events during flight.

У даній роботі виконана формальна постановка задачі прогнозування несприятливих авіаційних подій в польоті. Введено обмеження і допущення при розробці методу прогнозування несприятливих авіаційних подій в польоті. Запропоновано математичний апарат для побудови моделі прогнозування несприятливих авіаційних подій в польоті. В якості базового математичного апарату запропоновано використовувати рекурентні нейронні мережі RNN на базі модулів LSTM і згорткової нейронної мережі CNN. Аналіз можливостей мереж показав, що RNN на базі модулів LSTM ефективні,насамперед,при аналізі структурованого тексту, в якості якого розглядаються звіти про результати розслідування авіаційних подій. У свою чергу CNN ефективні при аналізі неструктурованого тексту, в якості якого в роботі розглядаються текстові повідомлення про ситуації в польоті за даними від зовнішніх джерел. Розроблено метод прогнозування несприятливих авіаційних подій в польоті на основі згорткових і рекурентних нейронних мереж RNN в контексті вирішення завдання прогнозування несприятливих авіаційних подій в польоті використовуються для початкового налаштування прихованого шару на структурованих навчальних прикладах в процесі навчання гібридної нейромережевої моделі, CNN використовуються в процесі безпосереднього функціонування гібридної нейромережевої моделі прогнозування несприятливих авіаційних подій в польоті.
Метод прогнозування несприятливих авіаційних подій в польоті на основі згорткових і рекурентних нейронних мереж
Keywords: hyperparameter; accuracy factor; гіперпараметр; показник точності